Differences between Staphylococcus aureus Isolates from Medical and Nonmedical Hospital Personnel - Cespedes, Christian (American Society for Microbiology, 2002)
It is unclear whether the levels of Staphylococcus aureus colonization of hospital personnel with patient exposure are increased or whether personnel become colonized with more antibiotic-resistant strains. Differences in nasal and hand carriage of S. aureus between medical and nonmedical hospital personnel were examined. No differences in nasal carriage between the two groups were found; however, there was a trend that suggested differences in the rates of hand carriage of S. aureus (18% of nonmedical personnel and 10% of medical personnel). Medical personnel were colonized with more antibiotic-resistant isolates than nonmedical personnel (mean, 2.8 versus 2.1 isolates [P < 0.03]), and the strain profiles indicated that they tended to be more clonal in origin, suggesting that exposure to hospital isolates alters the colonization profile.